Customer Relationship Management (CRM) in Tourism & Hospitality Industry - Singh, Lakhvinder; Dhankhar, Dinesh (Gyan Management Journal, 2014)
The Customer Relationship Management (CRM) has become the new gesture of marketing in an attempt to enhance customer satisfaction, build loyalty and increase profits. Several businesses especially tourism & hospitality implement customer relationship management programs to develop a trusting relationship among consumer to gain their confidence and increase repeat purchase. The present study will aimed to provide an overview of CRM in tourism & hospitality industry. The study is primarily based on secondary data sources. The study presented the appearance of CRM in tourism & hospitality industry, its paybacks and dark sides as well as also offers some valuable recommendations to make more viable.The study came up with the findings that travel and tourism companies have been make a sophisticated use of the possibilities and the capabilities of the applications of the CRM to the processing and management of the data and information collected from customers. CRM enable to target chosen market segmentsmore precisely, allowing management to streamline complex processes, automate workjlow, and increase productivity. The study also highlighted that there are many advocates for the adoption of customer relationship management (CRM) such as low cost, increased customer satisfaction & loyalty, more profitability, on the other hand some criticism also found such as lack of consistency, expensiveness & time consuming, lack of privacy, changing demands of customers etc.The study concluded that the future of CRM is bright if the organizations are willing to improve its current practices. They must build brand communities to encourage communication and increase loyalty among current and potential customers.